Prevalensi dan Intensitas Parasit pada Ikan Layur (Trichiurus lepturus) di Pasar Ikan Kedonganan, Bali - Rahmat, Hasbia; Julyantoro, Pande Gde Sasmita; Suryaningtyas, Endang Wulandari (Current Trends in Aquatic Science; Vol 3 No 1 (2020), 2020)
This study aims to determine the prevalence and intensity of parasitic infections in layur fish (T. lepturus) sold in Kedonganan Fish Market. Layur fish (T. lepturus ) were studied as many as 40 birds and identified in the Fisheries Science Laboratory, Faculty of Marine and Fisheries, Udayana University. Parasites observed were ectoparasites and endoparasites. The results of the research data were analyzed by calculating the difference in prevalence, intensity of infection, and correlation test to determine the relationship between length and intensity, weight with intensity, and descriptive calculation to determine the level of infection in various organs. The results showed that the prevalence of parasitic infections in layur fish (T. lepturus) marketed in the Kedonganan Fish Market was included in the ‘always’ category with a value of 95%. According to William and Bunkley (1996), this ‘always’ category illustrates that ordinary parasites infect fish by 90-98%. The intensity of parasitic infections was 815 parasitic individuals with an average intensity of 21.44 parasites / fish. After a correlation test, the relationship between the length and weight of the fish with the intensity of parasitic infection was positively correlated but with a weak relationship with values ??of 0.029 and 0.146, where each fish increased in length and weight, it did not necessarily increase the intensity of parasitic infections.